Pharmacokinetics and pharmacodynamics of meropenem in children with severe infection - Kongthavonsakul K. (2017)
© 2016 Elsevier B.V. and International Society of Chemotherapy This study aimed to describe the pharmacokinetic (PK) characteristics of meropenem in children with severe infections and to assess the pharmacokinetic/pharmacodynamic (PK/PD) profiles of various meropenem dosage regimens in these patients. Fourteen children with severe infections received intravenous (i.v.) bolus doses of meropenem (20 mg/kg/dose) every 8 h (q8h). Serum samples were obtained before and serially after the second dose of meropenem, and a population PK analysis was performed. The final model was used to simulate serum concentration–time profiles with various dosage regimens. The PK/PD target was to achieve a serum meropenem concentration higher than the minimum inhibitory concentration (MIC) of the causative organism (i.e. Pseudomonas aeruginosa and Enterobacteriaceae) for ≥40% of the dosing interval (40%T > MIC ). The median age and weight of the children were 6.0 years and 20.0 kg, respectively. Meropenem serum concentration–time profiles were best described by a two-compartmental model with first-order elimination. The simulations showed that the probabilities of target attainment (PTAs) for organisms with an MIC of 1 mg/L were 0.678 and 1.000 following i.v. bolus and 3-h infusion of meropenem (20 mg/kg/dose), respectively. Using a 3-h infusion of a 20 mg/kg/dose, the PTA was 0.999 and 0.765 for organisms with MICs of 4 mg/L and 8 mg/L, respectively. Meropenem given as i.v. bolus doses of 20 mg/kg/dose q8h appeared to be inadequate for PK/PD target attainment for organisms with an MIC of 1 mg/L. The simulations showed that meropenem administration via a 3-h infusion using the same dose improved the PTA.